Analisis Kesehatan Bank Mega Syariah Menggunakan Metode CAMEL Pada Periode 2020-2022 - Permana, Dirgama Mulya; Diana, Nana (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to analyze the health of Bank Mega Syariah using the CAMEL method during the period 2020-2022. This method involves assessing five dimensions: Capital Adequacy Ratio (CAR), Asset Quality (NPF), Management Quality (NOM), Earnings (ROA and BOPO), and Liquidity (FDR). The data used are the financial reports of Bank Mega Syariah. The research results indicate that the bank has a positive health status in all CAMEL dimensions during that period.In the Capital dimension, Bank Mega Syariah's CAR ratio increased from year to year, indicating sufficient capital to withstand loss risks. In the Asset Quality dimension, the NPF ratio experienced a significant decrease, indicating improved asset quality. In the Management Quality dimension, the NOM ratio fluctuated but remained within the healthy category. In the Earnings dimension, the ROA and BOPO ratios improved and remained in the very healthy category. Lastly, in the Liquidity dimension, the FDR ratio shows that the bank managed liquidity well.In conclusion, Bank Mega Syariah has achieved a good health status in all CAMEL dimensions during the 2020-2022 period. This positive performance can serve as a basis for the bank to continue maintaining and enhancing its quality and operational performance..